Research on Torque Characteristics of Magnetic Transmission Mechanism of Electric Submersible Centrifugal Pump - Qin, Haowei; Shao, Jun; Wang, Jiawei; Zhang, Qi (Scientific Journal of Technology, 2026)
This study presents a non-contact magnetic drive scheme designed to eliminate leakage at dynamic seals in Electric Submersible Centrifugal Pumps (ESPs) operating in high-temperature downhole environments (up to 200°C). The torque performance, magnetic field distribution, and eddy current losses of the proposed cylindrical magnetic coupling were investigated through integrated theoretical analysis and finite element (FE) simulations. A magnetic torque formula was derived theoretically, leading to the selection of Samarium-Cobalt (SmCo) permanent magnets and the determination of their axial length required for a 149.2 N·m torque output. FE simulations conducted in ANSYS Maxwell predicted a maximum static flux density of 2.397 T and a transient magnetic torque of 165 N·m, which deviates from the theoretical value by about 10.59%. The eddy current loss in the isolation sleeve was assessed to be 348.95 W. Three-dimensional simulations further highlighted the impact of end effects, prompting an optimization recommendation to use soft magnetic end caps for reduced flux leakage. The findings confirm the feasibility of the magnetic drive mechanism as an effective seal for ESPs, offering valuable design insights for magnetic transmission systems under extreme temperature and pressure.